Risk factors affecting long-term efficacy of ultrasound-guided high-intensity focused ultrasound treatment for multiple uterine fibroids - Zhenjiang Lin; Feng Xu; Yuan Yuan; Jiaojiao Peng; Jin Luo; Chunmei Gong; Dayong Chen; Yangyang Wang; Donghong Wang; Bing Yang; Lian Zhang (International Journal of Hyperthermia)
Objectives To investigate the long-term efficacy of ultrasound-guided high-intensity focused ultrasound (USgHIFU) for multiple uterine fibroids and the factors associated with recurrence.Materials and methods Five hundred and forty-nine patients with multiple uterine fibroids treated with USgHIFU from June 2017 to June 2019 were retrospectively analyzed. The Pictorial Blood Loss Assessment Chart (PBAC) was used to assess menstrual blood loss. The patients were asked to undergo pre- and post-USgHIFU magnetic resonance imaging (MRI) and complete routine follow-up after USgHIFU. Cox regression analysis was used to investigate the risk factors associated with recurrence.Results The median number of fibroids per patient was 3 (interquartile range: 3–4), and a total of 1371 fibroids were treated. Among them, 446 patients completed 3 years follow-up. Recurrence, defined as PBAC score above or equal to 100 and/or the residual fibroid volume increased by 10%, was detected in 90 patients within 3 years after USgHIFU, with a cumulative recurrence rate of 20.2% (90/446). The multi-factor Cox analysis showed that age was a protective factor for recurrence. Younger patients have a greater chance of recurrence than older patients. Mixed hyperintensity of fibroids on T2WI and treatment intensity were risk factors for recurrence. Patients with hyperintense uterine fibroids and treated with lower treatment intensity were more likely to experience recurrence than other patients after USgHIFU. No major adverse effects occurred.Conclusions USgHIFU can be used to treat multiple uterine fibroids safely and effectively. The age, T2WI signal intensity and treatment intensity are factors related to recurrence.